Challenges and solutions to the implementation of studies within a trial: The experiences of the PROMETHEUS programme. Issue 1 (January 2023) - Arundel, Catherine E; Clark, Laura; Coleman, Elizabeth; Doherty, Laura; Parker, Adwoa; Torgerson, David J
Background: Effective and efficient conduct of randomised controlled trials (RCTs) ensures accurate, timely results and prevents research waste. There is however limited evidence available to inform the design, conduct and reporting of RCTs. A self-contained, randomised Study Within A Trial (SWAT), embedded within a host RCT or cohort study, offers an opportunity to fill this evidence gap. While SWATs are generally easy to implement, a range of challenges to undertaking SWATs have also been identified, however there is limited detail regarding practical solutions to tackle these. Methods: Information and observations collected from PROMETHEUS members and participating trials, focusing on SWATs across a wide range of questions and settings, was reviewed to identify the challenges and solutions of delivery of a programme of SWATs. Results: A range of challenges to undertaking SWATs (e.g., obtaining governance approvals) were identified along with potential solutions to these, which were implemented accordingly during programme delivery. Central to the solutions to resolve SWAT challenges is education to develop knowledge and understanding in the wider research community on the importance, purpose, and key methodological principles in relation to SWATs. In addition, the sharing of experience, best practice or resources to prevent or help negotiate the barriers to undertaking SWAT evaluation is also recommended. Conclusions: Potential solutions to the barriers experienced in the design, conduct and implementation of a programme of SWATs have been identified. As more SWATs are completed, this will further develop evidence to support the mitigation or removal of barriers and in doing so this should increase the efficiency of randomised controlled trials.